VISUALIZATION OF INDONESIA'S GREEN ECONOMY INDEX (GEI) STATUS MAPPING FOR ECONOMIC TRANSFORMATION TOWARDS SUSTAINABLE DEVELOPMENT - Suyanto; Wiwik Budiarti; Jajuk Suprijati; Alda Raharja; Mustika Winedar (International Journal Management and Economic, 2025)
This study aims to map the status of the Green Economy Index (GEI) in Indonesia to support economic transformation towards sustainable development. Using the K-Means clustering method, this study analyzes GEI data from Dual Citizen at the global level and GEI from BAPPENAS at the national level. The results show that Indonesia is in the bottom seventh position globally, with a focus on air quality. Factors such as urbanization, the use of motor vehicles, and industrial activities are the main causes. In addition, at the provincial level, agricultural productivity is the biggest challenge in the green economy dimension. These findings confirm the need for integrated policies to address environmental issues and increase economic productivity. Policy recommendations include the transition to clean energy, the development of environmentally friendly public transportation, the improvement of low-carbon agricultural practices, and the strengthening of collaboration between stakeholders. This research provides important insights to support Indonesia's efforts to improve the GEI ranking and achieve the sustainable development goals.